Elaboration of hard yellow corn (Zea mays L.) Snacks enriched with giant squid (Dosidicus gigas) - Villafuerte, Ursula (2015)
Were made evaluation and determination of optimum control parameters for technological process of hard yellow corn snack (Zea mays L.), enriched with giant squid (Dosidicus gigas), through sensory tests in each study phase and finally a physico-chemical analysis to know its composition. . An innocuous product was obtained, resulting from the elaboration process that comprises the following operations: pretreatment of maize (nixtamalization) and of giant squid (precooked, grinding), homogenization (80% nixtamal and 20% cuttlefish), molding and gelatinization (to 70°C during 30 minutes), cool-down, lamination, fry-up, and addition of flavor, (2% sault), packing, storage. With the pulp of the giant squid (Dosidicus Gigas), was achieved enrich the hard yellow corn snack (Zea mays L.), increasing the protein level in 5,17 g/100 g of snack, in comparison to the commercial product. As result, the optimum sensory responses were chosen to define the optimum parameters of control, that were determined through organoleptic analysis of sensory profile, as well as through physico-chemical and microbiological analysis.